Immune inflammation indicators and ALBI score to predict liver cancer in HCV-patients treated with direct-acting antivirals. Issue 5 (May 2019) - Casadei Gardini, Andrea; Foschi, Francesco Giuseppe; Conti, Fabio; Petracci, Elisabetta; Vukotic, Ranka; Marisi, Giorgia; Buonfiglioli, Federica; Vitale, Giovanni; Ravaioli, Federico; Gitto, Stefano; Verucchi, Gabriella; Lenzi, Marco; et al.
Abstract: Background: Unexpectedly high occurrence or recurrence rate of hepatocellular carcinoma (HCC) has been observed in patients with chronic hepatitis C receiving direct-acting antivirals (DAAs) therapy. Aims: We evaluated the predictive value of albumin-bilirubin (ALBI) score and immune-inflammation indicators to identify the risk of occurrence or recurrence of HCC in patients treated with DAAs in a real life setting. Methods: In this retrospective cohort study, we analysed data from 514 patients with cirrhosis who were prospectively enrolled for treatment with DAAs. We assessed baseline neutrophil to lymphocyte ratio (NLR), systemic immune-inflammation index (SII), platelet to lymphocyte ratio (PLR), aspartate aminotransferase-lymphocyte ratio (ALRI) index and ALBI score. Results: In patients with no history of HCC (N = 416), increased AST, bilirubin, ALRI, and ALBI score, and decreased albumin and platelets were significantly associated with an increased risk of HCC development, at univariate analysis. At multivariate analysis, increase in ALBI grade (p = 0.038, HR: 2.35, 95% CI: 1.05–5.25) and decrease in platelets (p = 0.048, HR: 0.92, 95% CI: 0.85–1.0) were independently associated with HCC development. In patients with previous HCC (N = 98), adjusting for the time from HCC treatment, increased ALRI (p = 0.008, HR: 1.05, 95% CI: 1.01–1.09) was significantly associated with a risk of recurrence. Conclusion: ALBI score, platelet count and ALRI are promising, easy to perform and inexpensive tools for identifying patients with higher risk of HCC after treatment with DAAs.